Research on Optimal Control Strategy of Energy Storage for Improving New Energy Consumption - Liantao LIU; Fei LIU; Ping JI; Weifang LIN; Xiangcheng ZHANG; Xu TIAN; Fei GAO (Zhongguo dianli)
To achieve the carbon peak and neutrality goals by improving the new energy consumption, a decoupling based optimal control method of energy storage is proposed. For the problem of solving the nonlinear model of optimal control, a linearization and simplification method based on decoupling is presented. Using the enumeration optimization and iterative load flow, the constraint of energy storage operation is compacted, which guarantees the objective of new energy consumption promotion and operation security constraints. The case analysis shows that the simplified linear model is consistent with the original nonlinear model and the difficulty of solving the high-order optimal control model is reduced. It ensures the fast and reliable decision of energy storage to promote the new energy consumption, and increases the comprehensive benefits of new energy and energy storage.